1999
DOI: 10.1002/(sici)1521-3749(199902)625:2<321::aid-zaac321>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Die Umsetzung von Dialkylaluminiumchloriden mit Bis(trimethylsilyl)hydrazin: Bildung von Addukten R2AlCl · NH2NHSiMe3 mit dem thermisch unbeständigen Trimethylsilylhydrazin

Abstract: Bis(trimethylsilyl)hydrazin reagiert mit Dialkylaluminiumchloriden R2AlCl [R = CH2CMe3, CMe3 und CH(SiMe3)2] nicht unter Bildung von Trimethylchlorsilan, sondern unter Dismutierung zu Tris(trimethylsilyl)hydrazin und Trimethylsilylhydrazin. Das sterisch weniger hoch abgeschirmte NH2NHSiMe3, das in freier Form unbeständig ist, wird durch die koordinativ ungesättigten Aluminiumverbindungen unter Komplexierung stabilisiert. Dabei entstehen die Addukte R2AlCl · NH2NHSiMe3, die für R = CMe3 und CH(SiMe3)2 kristalls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 16 publications
4
21
0
1
Order By: Relevance
“…[10] As is reported here, these adducts are excellent starting materials for the synthesis of aluminium hydrazides under mild conditions. Scheme 1 …”
Section: Introductionmentioning
confidence: 57%
See 2 more Smart Citations
“…[10] As is reported here, these adducts are excellent starting materials for the synthesis of aluminium hydrazides under mild conditions. Scheme 1 …”
Section: Introductionmentioning
confidence: 57%
“…The adduct 2, bis(trimethylsilyl)hydrazine and (Me 3 C) 2 AlCl were synthesized as described in refs. [10,11,21] . Phenylhydrazine (Aldrich) was distilled prior to use, and the solution of n-butyllithium in n-hexane (Aldrich) was used without further purification.…”
Section: Quantum Mechanical Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[14] Moreover, Uhl et al found that the reaction of tBu 2 AlCl with H 2 NNHSiMe 3 produced tBuCl 2 -Al·NH 2 ϪNHSiMe 3 , a compound that is analogous to compound 1. [61] It is interesting that the tert-butylhydrazine removes MeGaCl 2 from the equilibrium in Equation (1) while the lithium hydrazide Li(Me 3 Si)NϪNHϪtBu adds to trimethylgallium and not to a methylgallium chloride molecule. This can be rationalized as follows.…”
Section: Discussionmentioning
confidence: 99%
“…This compound was isolated and fully characterized. Nevertheless, it is once again an unexpected product, as shown in Equation (10). Compound 9 can be regarded as the adduct of a bis(dimethylindium) oxide (diindoxane) with lithium tris(trimethylsilyl)hydrazide.…”
Section: Synthesismentioning
confidence: 99%